Economic Growth and the Contribution of the Forest Sector in India - Mohanty, R. N. (Indian Forester, 1973)
Economic growth of a nation is measured by the rate of sustained long-term rise in total product or still better by product per capita. Associated with this are also large aad rapid shifts that occur in the structure of the economy and the pattern of economic flows between it and rest of the world. The three aspects are interrelated. Judged by these standards the growth of the India economy during the last 21 years of modern planning experience has been significant and very eacouraging. During this period, the national and per capita income rose significantly; so also the value and volume of exports and grows capital formation. Even then, a very recent study by the International Monetary Fund and World Bank grorp showed that as regard per capita G.N.P. in 1969 and its annual rate of growth during 1960-69 was coacerned, India was among those in the lower bracket. So far as the forest sector was concerned, its contribution to the growth of the national income haa been rather too small, in relation to its size. But what is disturbing is that during tha last two years, the annual rate of growth in this sector has been quite low-2.1 percent in 1969-70 and 3.5 percent in 1970-71 as agnist 5.3 percent and 4.8 per cent for the whole economy. The leisurely pace at whlch the country’s forest sector has grown is no longer adequate to keep ahead of rising internal and global demands for better existence. In spite of large areas uader forests, tbe forest sector in India is most likely not the one where the war for lont-term economic development can be won or lost; nevertheless this is a sector with vast unexploted potential, capable of much greater output and income at comparatively short periods with further improvements in inputs, investments and methods that will create the "big push". This paper stresses the need to identify the possible and direction of development and selection of strategies for accelerating growth in this sector for the overall development of the country’s economy in light of experlience a gained. Statistical data have been emphasised because economic growth is essentially a quantitative concept.